The Effect Of The Flashcard Learning Method On Elementary School Students English Writing Skills - Endang Sri Andayani (STIE Amkop Makassar, 2023)
Learning English is given to children from an early age, so learning should be adapted to the child's development. Writing skills in English is the most difficult skill because in writing students must have other skills as a component of writing skills such as vocabulary, grammar, spelling, and so on. This study aims to determine the effect of the flashcard learning method on the English vocabulary writing skills of elementary school students. The research design used is pre-experimental. This study used a sample of 30 class III students, while the research was carried out in 4 stages, namely the first stage was to conduct a pre-test. The second stage is to provide treatment using flashcard media in learning English. The third stage is to do a post-test after being given treatment. The final stage is to carry out a comparative analysis between the results of the pre-test and post-test to see the effect of flashcard media and the answerability of the research objectives. The results of the study proved that the flashcard learning method affected elementary school students' English vocabulary and writing skills.